Contextualization of Ta'zir and Amar Ma'ruf Nahi Munkar to Address Illegal Online Loans - Achmad Bissri Fanani; Imam Shobari; Iqbalul Muid; Musthofa Ahmad Al-Mu’thi; Moch. Rafli Nazillur Roikhan (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Financial technology (fintech) has transformed the financial services industry, offering convenience and broader access. Specific background: However, the rapid growth of online loans has also given rise to illegal lending practices, marked by exorbitant interest rates, privacy violations, and exploitative collection methods, causing serious economic and psychological harm. Knowledge gap: Previous studies have examined illegal loans from legal, economic, and social perspectives, yet few have analyzed solutions through the framework of industrial fiqh. Aims: This study seeks to contextualize the concepts of amar ma’ruf nahi munkar (enjoining good and forbidding wrong) and ta’zir (discretionary punishment) as frameworks to address the proliferation of illegal online loans. Results: Findings show that economic pressures, consumptive lifestyles, and low financial literacy are primary factors driving communities into debt traps. Illegal loans are deemed unlawful in Sharia due to elements of riba, gharar, and zulm. Novelty: By applying classical fiqh principles within the theory of industrial fiqh, this study introduces practical programs: financial literacy campaigns as amar ma’ruf and strengthened regulation and law enforcement as ta’zir. Implications: These approaches highlight the relevance of fiqh in modern socio-economic challenges, offering a Sharia-based, preventive, and corrective framework to protect society from exploitative financial practices. Highlights: Illegal online loans cause economic, social, and psychological harm. Fiqh principles provide preventive and corrective solutions. Novelty lies in contextualizing amar ma’ruf and ta’zir within industrial fiqh. Keywords: Fintech, Illegal Online Loans, Industrial Fiqh, Amar Ma’ruf Nahi Munkar, Ta’zir